Comparison of human epidermal growth factor receptor 2 and cancer stem cell markers like CD44 and CD133 expressions with clinicopathological parameters in gastric cancer - Gecer, Melin; Büyükpınarbaşılı, Nur; Turna, Seval; Beşiroğlu, Mehmet; Gucın, Zuhal (The European Research Journal, 2023)
Objectives: Gastric carcinoma (GC) is the fourth most common cause of cancer-related tumor deaths worldwide. The prognostic significance of CD44, CD133 and human epidermal growth factor receptor 2 (HER2) expression in GC remains controversial. Therefore, we aimed to investigate the relationship of CD44, CD133 and HER2 expression with clinicopathological features in metastatic and non-metastatic GC patients. Methods: A total of 139 patients with GC (68 with metastasis, 71 without metastasis) diagnosed were retrospectively analyzed. CD44 and CD133 expression were determined by immunohistochemical method in all cases. In addition, HER2 overexpression of the tumor was evaluated in patients with metastatic GC. Results: The CD133 positivity rate was 90.6% (n = 126) when all cases were considered, and that for CD44 was 84.9% (n = 118). There was no difference in CD133 and CD44 positivity (intensity or density) rates and between the total scores of metastatic and non-metastatic patients with GC (p > 0.05). HER2 positivity in metastatic cases was detected in 49 (70.1%) patients by immunohistochemical method. No correlation was found between CD133 total score and age, tumor size or depth, and HER2 scores in metastatic or non-metastatic cases (p > 0.05). In the correlation analyzes performed with CD44 scores, only a borderline significant correlation was found between CD44 scores and tumor size (r:0.175; p = 0.047) in non-metastatic cases. Conclusions: We demonstrated associations between CD44/CD133 expression and histological grade in all patients, between CD44 and tumor size in non-metastatic patients, and between HER2 and intestinal type (Lauren) in metastatic patients. The results of this study need to be confirmed by multicenter studies including large case series.